A rare case of acute respiratory distress syndrome due to chlorine gas inhalation: Rapid progression with favorable ICU outcome - Dung Thai Pham; Bang Ngoc Dao; Dung Tien Nguyen; Ba Van Dang; Dung Tien Le; Hung Manh Do; Loc Tich Hoang; Minh Tuan Ngo; Duong Minh Vu (Respiratory Medicine Case Reports)
Acute respiratory distress syndrome (ARDS) secondary to chlorine gas inhalation is a rare yet critical condition that can lead to severe respiratory failure if not managed promptly. This case report presents a 43-year-old male who developed ARDS after accidental exposure to chlorine gas during pool maintenance. The patient's condition deteriorated rapidly, with symptoms progressing to acute pulmonary edema and severe hypoxemia, requiring immediate transfer to the intensive care unit (ICU). Initial treatment included non-invasive ventilation, but the patient soon required tracheal intubation and mechanical ventilation. Despite the rapid disease progression, the patient responded well to aggressive ICU management, including oxygen therapy, mechanical ventilation, and pharmacological support. Remarkably, within seven days, the patient fully recovered and was discharged in stable condition. This case highlights the potential for a good prognosis in ARDS due to chlorine gas inhalation compared to other etiologies, emphasizing the importance of timely intervention and specialized care in the ICU.